The Role of Neutrophils in the Induction of Specific Th1 and Th17 during Vaccination against Tuberculosis - Trentini, Monalisa M.; de Oliveira, Fábio M.; Kipnis, André; Junqueira-Kipnis, Ana P. (Frontiers in Microbiology, 2016)
Mycobacterium tuberculosis (Mtb) causes tuberculosis (TB), a disease that killed more than 1.5 million deaths worldwide in 2014, and the Bacillus Camette Guérin (BCG) vaccine is the only currently available vaccine against TB. However, it does not protect adults. Th1 and Th17 cells are crucial for TB control, as well as the neutrophils that are directly involved in DC trafficking to the draining lymph nodes and the activation of T lymphocytes during infection. Although several studies have shown the importance of neutrophils during Mtb infection, none have shown its role in the development of a specific response to a vaccine. The vaccine mc2-CMX was shown to protect mice against Mtb challenge, mainly due to specific Th1 and Th17 cells. This study evaluated the importance of neutrophils in the generation of the Th1- and Th17-specific responses elicited by this vaccine. The vaccine injection induced a neutrophil rich lesion with a necrotic central area. The IL-17 KO mice did not generate vaccine-specific Th1 cells. The vaccinated IL-22 KO mice exhibited Th1- and Th17-specific responses. Neutrophil depletion during vaccination abrogated the induction of Th1-specific responses and prohibited the bacterial load reduction observed in the vaccinated animals. The results show, for the first time, the role of neutrophils in the generation of specific Th1 and Th17 cells in response to a tuberculosis vaccine.